Pemahaman Guru dan Orang Tua Mengenai Alternatif Strategi Reward dan Punishment yang Lebih Positif di Sekolah TK di Cikarang Selatan - Juariah, Siti; Halimah, Halimah (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2024)
Parents and teachers play a crucial role in shaping a quality generation. Both must complement each other in guiding and nurturing the potential of children. The aim of this research is to provide an understanding to teachers and parents in educating children using a more appropriate alternative method, namely reward and punishment. The reward and punishment method aims to discipline and educate children with love and not to scare them. Appreciation and punishment will greatly influence the way children think and behave in achieving educational goals with character. This research uses a qualitative method with data collection techniques through observation and literature review approaches. Data collected from both approaches are then systematically analyzed and conclusions are drawn based on the results obtained, supplemented by literature studies obtained from relevant sources according to our research topic. The results of the study indicate that there are deficiencies in understanding the concepts of reward and punishment from both kindergarten teachers and parents. Some findings include low awareness, lack of knowledge, and gaps in understanding, thus requiring understanding and implementation of positive reward and punishment strategies in the kindergarten environment, both through training and education attended by teachers and parents.